Caracterização funcional da E3 ubiquitina ligase LinfCRL1 de Leishmania infantum - Alves, Ellen Gomes (Universidade Federal de São Carlos, 2024)
CRL-type E3 ubiquitin ligases are enzymatic complexes composed of four main proteins: SKP1, CUL1, RBX1, and an F-box protein, which binds to SKP1 through its F-box domain, recruiting substrates for ubiquitination. The ubiquitination process occurs in multiple steps and is highly regulated, involving three essential enzymes: E1 (ubiquitin-activating enzyme), E2 (ubiquitin-conjugating enzyme), and E3 (ubiquitin ligases), which play a crucial role in recognizing and transferring ubiquitin to the target protein. This process ensures the regulation of target protein function and fate, directing them to the proteasome for degradation or modulating their functions. CRLs are the most studied class of E3 ligases in eukaryotes and are responsible for regulating various processes, including the cell cycle. In Leishmania parasites, this class of enzymes has not yet been described. In this study, we identified orthologous genes to human CRLs in L. infantum, showing conservation of interaction regions between the complex proteins. We generated knockout strains of L. infantum for the genes LINF_110018100 (LinfSKP1), LINF_21000530 (LinfRBX1), and LINF_240029100 (LinfCUL1) using the CRISPR-Cas9 system. The knockout of LinfCUL1 resulted in a viable strain but showed impaired promastigote proliferation and led to an accumulation of cells in the late S phase of the cell cycle, as evidenced by flow cytometry and EdU assays. Furthermore, LinfCUL1 knockout induced rosette formation in cell culture and significantly interfered with promastigote infectivity. Additionally, knockouts of LinfSKP1 and LinfRBX1 resulted in non-viable parasites, suggesting that these genes are potentially essential for the parasite. The add-back strain of LinfCUL1 restored the wild-type phenotype in terms of promastigote proliferation, which did not occur when a mutant LinfCUL1 (LinfCul1 DN), incapable of forming the LinfCRL1 complex, was used, confirming that the knockout effect is related to the function of the LinfCRL1 complex. Our results indicate that CRL genes are associated with cell cycle regulation, viability, and infectivity in L. infantum.
Functional characterization of Cullin-1-RING ubiquitin ligase (CRL1) complex in Leishmania infantum
Keywords: Leishmania infantum; CRISPR-Cas9; Cullin-RING ligases; Culina-RBX ligases; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA MOLECULAR